From Feeding the Hungry to Nourishing All People: A Tribute to Dr M. S. Swaminathan - Wismen, Bendula; Thilsted, Shakuntala (CGIAR System Organization, 2025)
CGIAR Nutrition, Health and Food Security Impact Platform organized a special tribute session to Dr M. S. Swaminathan at the 2024 Norman E. Borlaug Dialogue Week of Events/ 2024 World Food Prize. Dr. M. S. Swaminathan was the inaugural World Food Prize Laureate in 1987, recognized for his significant contribution in the Green Revolution, and his research on important crops including potato, wheat and rice. His contributions went beyond improving breeding lines; for example, the inclusion of women in rice farming systems was important for him to realize his goal of 'a world without hunger'. These approaches continued through the M. S. Swaminathan Research Foundation, including the use of science and technology in nature-based solutions to improve agricultural production.